Potato biopolymers obtaining an alternative to the development of environmental friendly materials - Alarcón, Hugo (2014)
In the present work, the first results of the biopolymers obtained from the starches extracted from potatoes and cassava are presented, these were analyzed by the IR spectroscopy technique, observing that in both cases they present the same starch characteristics, so potato starch was chosen because it is a From this starch films with an approximate thickness of 50 microns were obtained, which were characterized by elongation and tensile techniques with maximum elongation values of 62% and a maximum tensile force of 10 Newton, it was also characterized by IR spectroscopy finding the peaks Characteristic of cellulose, the films have a high transmittance in the visible range, atomic absorption analyses show the harmlessness of the films obtained.